The right of women to vote in the Quran and Sunnah: a case study in Malaysia / Ahmed S. A. Alqodsi and Sharifah Norshah Bani Syed Bidin - Alqodsi, Ahmed S. A.; Syed Bidin, Sharifah Norshah Bani (Academy of Contemporary Islamic Studies (ACIS), Universiti Teknologi MARA (UiTM), 2024)
The text of the Quran and the Sunnah of the Prophet PBUH emphasize human rights, particularly, women’s rights, with the Maqasid of Shariah law aiming to preserve these rights for human dignity. This research examines how the Quran and Sunnah guarantee human rights, explores the legitimacy of women’s right to vote, and discusses their participation in Malaysian elections. This article employs a descriptive approach by identifying the issues and collecting scientific materials from primary and secondary sources about human rights in general and women’s rights in particular. It also follows an analytical approach in studying and analysing issues to reach real results and a clear understanding of the subject. The study reveals that the texts of the Quran and Sunnah guarantee the human rights of both men and women in elections while controlling the appropriate conditions therein. The strength of the opinion of contemporary scholars on the legitimacy of women’s right to participate in elections today is due to the clear stability that their participation achieves in their country, supporting aspirations, and caring for women’s dignity. The article also demonstrates the political awareness of women in Malaysia regarding their exercise of the right to vote and their positive impact on political participation in Malaysia.